The Role of the Criminal Investigation Unit in Enhancing the Quality of Public Services in Handling Theft Cases - Syah, Syahiruddin (PINISI Discretion Review, 2024)
The purpose of this study is to assess the public service performance of the employees at the Luwu Utara Police Department and the efforts made in addressing motor vehicle theft in Luwu Utara. This research employs a qualitative approach with descriptive-analytical methods. Data was collected from several informants, including the Chief of Police of Luwu Utara, the Deputy Chief of Police, members of the Luwu Utara Police Department, and the local community. The findings of the study indicate that the public service performance of the employees at the Luwu Utara Police Department is generally satisfactory. This conclusion is based on three indicators: responsiveness, responsibility, and accountability. The responsiveness of the officers, or their ability to understand and address the needs and desires of the community, was found to be lacking. However, the responsibility of the officers, demonstrated by their commitment to carrying out their duties, was strong. Additionally, the accountability of the officers, shown by their specialized skills in performing their respective roles and functions, was well-established.